Nature and cause of CO2 emission in Eastern Africa: Role of tourism and afforestation towards reduce CO2 emission - Tasin Safwath Chowdhury; Mst. Jannatul Mawa; Rahat Ul Islam; Mr Imtiaz Uddin; Md. Hasanur Rahman (Social Sciences and Humanities Open)
Primary purpose of this study is to investigate the nature and causes of environmental deterioration in selected Eastern African countries, specifically how tourism and afforestation can help decrease CO2 emissions, using panel data from 1990 to 2021. The study examines how tourism can lead to environmental harm by causing habitat destruction and pollution, while also considering its role in promoting sustainable development and conservation. Tourism is variable and has a positive effect on CO2 emissions. A one percent increase in tourism in Eastern African countries often leads to a corresponding 0.08 percent rise in CO2 emissions. The research examines how effective afforestation is in reducing greenhouse gas emissions and improving ecosystem resilience. A one percent increase in the service sector contribution results in a 0.82 percent reduction in CO2 emissions. In addition, a one percent increase in forest area tends to reduce CO2 emissions by 0.53 percent in Eastern African countries. Afforestation helps to capture carbon dioxide, supports ecosystem restoration, and supports ecosystem restoration and biodiversity protection. The research thoroughly analyzes these aspects to offer insights and recommendations for policymakers and stakeholders to undertake effective actions to reduce environmental degradation and promote sustainable development in Eastern Africa.